Older Adults and their Retirement from the Labor Market in Mexico - Román-Sánchez, Yuliana Gabriela; Montoya-Arce, Bernardino Jaciel; Cuauhtémoc Gaxiola-Robles-Linares, Sergio; Lozano-Keymolen, Daniel (Sociedad y Economía, 2019)
The objective of this article is to analyze the process of transition from occupation to inactivity or vice versaof the older adult population in Mexico and the variables that intervene in these changes. Specifically, the probabilities of transition between four states were estimated: 1) Employed, 2) Pensioner or retired, 3) Permanent disability and 4) in charge of household chores. To achieve the above, the panel data of the National Survey of Occupation and Employment (ENOE) was used. Transition matrices of the four states were estimated to determine the probability for passing to each of them, considering the sex differences. The results suggest a relative stability of employed older adults. Men are twice as likely to retire and be pensioners than women, also there is a notorial stagnation of women in household chores. Variables such as sex and area of residence negatively influence the retirement of older adults from the labor market.